2003
DOI: 10.1071/ar02168
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating physicochemical constraints of Calcarosols on wheat yield in the Victorian southern Mallee

Abstract: Soil salinity, sodicity, and high extractable boron (B) are thought to reduce wheat yields on alkaline soils of south-eastern Australia; however, little quantitative information on yield penalties to edaphic constraints is available. The relationships between wheat yield of a B-tolerant cultivar and soil physicochemical conditions in the Victorian Mallee were explored using ridge regression analysis, using natural variation in the field. Wheat yields in the survey ranged from 1.3 to 6.1 Mg/ha, with low yields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 29 publications
6
47
3
Order By: Relevance
“…Presence of subsoil constraints generally results in poor harvest index, resulting from either smaller grain size or reduced grain yield due to restricted ability of the roots to extract stored water in the subsoil during grain fill (Nuttall et al 2003). However, in the present study, the relatively high harvest index reported for 5 crop species (Table 3) could be due to soft finish during 2004 (Fig.…”
Section: Effects Of Subsoil Constraints On Water Extraction and Crop contrasting
confidence: 51%
“…Presence of subsoil constraints generally results in poor harvest index, resulting from either smaller grain size or reduced grain yield due to restricted ability of the roots to extract stored water in the subsoil during grain fill (Nuttall et al 2003). However, in the present study, the relatively high harvest index reported for 5 crop species (Table 3) could be due to soft finish during 2004 (Fig.…”
Section: Effects Of Subsoil Constraints On Water Extraction and Crop contrasting
confidence: 51%
“…This suggests that significant yield losses are likely to occur when current lentil varieties are grown on such soils, and the greater B-tolerance identified in this study is significant. Targeted breeding efforts to improve B-tolerance of wheat have been in progress since the mid 1980's and a recent study by Nuttall et al (2003a) concluded that the B-tolerance level of the wheat variety Frame was sufficiently high that yield was poorly correlated with soil-B concentration. This indicates that levels of B tolerance in current wheat varieties such as Frame are adequate to alleviate yield losses due to B in southern Australia.…”
Section: Discussionmentioning
confidence: 98%
“…Comparing the grain yields of both barley and wheat genotypes grown at the sodic site to the grain yields at the non-sodic site, significantly higher ESP to a depth of 0.6 m in the sodic soil resulted in reduced grain yields of both barley and wheat genotypes. It has been shown that ESP > 6% in the surface soil [25] and >19% in the subsoil [9] reduces the grain yield of most crops. Grain yield on sodic soils is often less than 50% of the potential yield [29].…”
Section: Genetic Variation Indicates That the Crop Performance Under mentioning
confidence: 99%